2002
DOI: 10.1002/jcla.10028
|View full text |Cite
|
Sign up to set email alerts
|

Use of the eie‐recombinant‐chagas‐biomanguinhos kit to monitor cure of human chagas’ disease

Abstract: We used the EIE-Recombinant-Chagas-Biomanguinhos kit (EIE-Rec kit) developed by the Oswaldo Cruz Foundation, Brazil, to monitor cure of chagasic patients who were treated during the acute phase of T. cruzi infection. Treated patients were previously studied by parasitological and serological tests and classified as cured patients (CP) (n = 10), dissociated patients (DP) (n = 6), and noncured patients (NCP) (n = 6). When sera of these patients were assayed by EIE-Rec kit all sera from NCP and all sera from CP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…A kit for diagnosis of chronic Chagas disease called EIE-Recombinante-ChagasBiomanguinhos ® (Rec-ELISA), which uses these antigens in combination (CRA + FRA), has been developed and produced by Biomanguinhos, at the Oswaldo Cruz Foundation (Fiocruz), in Rio de Janeiro, Brazil. This kit is based on an enzyme immunoassay and direct ELISA and has been evaluated for diagnosis of T. cruzi infection ) and as a follow-up test for monitoring chemotherapy (Silva et al 2002), with excellent results. The Rec-ELISA was also compared with the conventional ELISA(Con-ELISA) and IHA, with a view to minimizing the number of inconclusive results.…”
Section: What Still Needs To Be Done Regarding Diagnosis?mentioning
confidence: 99%
See 2 more Smart Citations
“…A kit for diagnosis of chronic Chagas disease called EIE-Recombinante-ChagasBiomanguinhos ® (Rec-ELISA), which uses these antigens in combination (CRA + FRA), has been developed and produced by Biomanguinhos, at the Oswaldo Cruz Foundation (Fiocruz), in Rio de Janeiro, Brazil. This kit is based on an enzyme immunoassay and direct ELISA and has been evaluated for diagnosis of T. cruzi infection ) and as a follow-up test for monitoring chemotherapy (Silva et al 2002), with excellent results. The Rec-ELISA was also compared with the conventional ELISA(Con-ELISA) and IHA, with a view to minimizing the number of inconclusive results.…”
Section: What Still Needs To Be Done Regarding Diagnosis?mentioning
confidence: 99%
“…A number of serological techniques have been evaluated as possible substitutes for the CoML test by using an ELISA with purified (Gazzinelli et al 1993) and recombinant antigens (Krautz et al 1995, Silva et al 2002. Silva et al (2002) showed that when the serum from patients previously investigated using parasitological and serological tests and classified as CP (n = 10), DP (n = 6) and NCP (n = 6) was assayed using the EIE-Rec kit, all the serum samples from NCPs tested positive and all the samples from CP tested negative.…”
Section: What Remains To Be Done With Regard To Follow-up Studies?mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples collected at different periods of time during this human T. cruzi infection were valuable for evaluating the success of the specific therapy and to establish a cure; all tests became negative after 300 days. Several other purified antigens from T. cruzi are commercially available for the diagnosis of Chagas disease using ELISA, but only one has been evaluated in controlled clinical trials using treatedpresumably-cured patients (Silva et al 2002, Gadelha et al 2003, Lorena et al 2008. The data are summarized in Table V and discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…In treated patients considered cured, all tests were negative; in the dissociated patients (DP), CoML was negative and CS persistently positive. The ELISA data (Silva et al 2002) were also negative in all sera from the 10 cured patients and in all sera from non-chagasic subjects. In addition, all the untreated and the treated noncured patients were positive.…”
Section: Why Does Cs Remain Positive After Drug Treatment and Cure Ofmentioning
confidence: 90%